Princeps exegetarum a język hebrajski na podstawie "Quaestiones hebraicae in Genesim" - Jóźwiak, Magdalena (Vox Patrum, 2016)
In this article we have tried to show St. Jerome’s knowledge of Hebrew language basing on selected fragments of Quaestiones Hebraicae in Genesim (PL 23, 935A - 1010A). First of all, we tried to show how St. Jerome deals with text during translation of the Bible from Hebrew into Latin. In his work, St. Jerome tries to give the etymology of almost every proper name that appears in a given verse commented by him. St. Jerome’s effort and merit in this field are of course enormous, but sometimes even he put wrong etymology. We have shown how the author of Vulgate explains the most common Hebrew expressions and how he attempts to improve the Septuagint, and we also put forward purely grammatical considerations that the commentator included in Quaestiones Hebraicae. St. Jerome’s knowledge of the sacred language – perfect for those times – is a reason that in case of any doubts he is in favor of the superiority of hebraica veritas over translations of the Bible.